Analisis Daya Saing pada Usahatani Padi Tadah Hujan dan Usahatani Padi Irigasi di Klaten (Jurnal Agribisnis Indonesia, 2022)
One of the strategic agricultural development programs is food self-sufficiency. This self-sufficiency is called rice self-sufficiency because rice is the main food ingredient in food self-sufficiency. Rice is a strategic food crop for the creation of rice self-sufficiency in in Indonesia. The purpose of this study was to analyze competitiveness based on competitive, comparative, and sensitivity advantages in rainfed and irrigated rice fields in Klaten district. The method used in determining the sample was done by purposive sampling. Data analysis used the Policy Analysis Matrix (PAM) method and sensitivity analysis. The results showed that the rainfed lowland and irrigated rice fields in Klaten Regency had competitive and comparative advantages. The sensitivity analysis saw that when there was a 20 percent decrease in output in rainfed rice, it was no longer competitive because the PCR value became 1,01 from 0,80 while irrigated rice fields remained competitive with a PCR value of 0,71 from the previous 0,56. For rainfed lowland rice farming, it is necessary to have additional technology to increase production during a longer dry season or lower rain intensity so that production does not decrease due to water shortages in rainfed rice fields which make it unable to compete competitively and comparatively.